2020
DOI: 10.15628/holos.2020.9737
|View full text |Cite
|
Sign up to set email alerts
|

MULTIVARIATE AND CANONICAL MODELS APPLIED TO CORN: BENEFITS OF GREEN MANURE WITH Vigna unguiculate

Abstract: Este é um artigo publicado em acesso aberto sob uma licença Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The genotype × environment interaction was not significant only for spike height, demonstrating the effect of genetic variability for almost all traits (Table 4). Studies carried out with the maize crop have also found genetic variability among phenological, morphological, production and tassel traits (SOUZA et al, 2015;ALVES et al, 2016a;ALVES et al, 2016b;ALVES et al, 2017;CARVALHO et al, 2017;XU et al, 2017, KHAN et al, 2018NASCIMENTO-JÚNIOR;MÔRO;MÔRO, 2018;ÖNER, 2018;CREVELARI et al, 2019;TROYJACK et al, 2019;FERREIRA et al, 2020;CARVALHO et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The genotype × environment interaction was not significant only for spike height, demonstrating the effect of genetic variability for almost all traits (Table 4). Studies carried out with the maize crop have also found genetic variability among phenological, morphological, production and tassel traits (SOUZA et al, 2015;ALVES et al, 2016a;ALVES et al, 2016b;ALVES et al, 2017;CARVALHO et al, 2017;XU et al, 2017, KHAN et al, 2018NASCIMENTO-JÚNIOR;MÔRO;MÔRO, 2018;ÖNER, 2018;CREVELARI et al, 2019;TROYJACK et al, 2019;FERREIRA et al, 2020;CARVALHO et al, 2022).…”
Section: Resultsmentioning
confidence: 99%